2009
DOI: 10.1016/j.jcis.2009.07.066
|View full text |Cite
|
Sign up to set email alerts
|

Influence of iron oxide nanoparticles on the rheological properties of hybrid chitosan ferrogels

Abstract: Magnetite nanoparticles have been successfully synthesized in the presence of chitosan using an in situ coprecipitation method in alkali media. This method allows obtaining chitosan ferrogels due to the simultaneous gelation of chitosan. The chitosan concentration has been varied and its effects on the particle synthesis investigated. It has been demonstrated that high chitosan concentrations prevents the formation of magnetite due to the slow diffusion of the alkali species through the viscous medium provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 50 publications
3
42
0
Order By: Relevance
“…The formation of Fe 3 O 4 nanoparticles within preformed dextran hydrogel beads (Dou et al, 2008) resulted in superparamagnetic composite particles with magnetization saturation values comparable to those of Fe 3 O 4 nanoparticles prepared via typical coprecipitation routes, which renders these materials interesting for applications in the biomedical field. The formation of magnetite nanoparticles within chitosan using the coprecipitation route was found to be dependent on the concentration of this polysaccharide (Hernandez et al, 2009). Above a chitosan content of 3 wt%, a non magnetic iron hydroxide was formed instead of magnetite.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 96%
See 1 more Smart Citation
“…The formation of Fe 3 O 4 nanoparticles within preformed dextran hydrogel beads (Dou et al, 2008) resulted in superparamagnetic composite particles with magnetization saturation values comparable to those of Fe 3 O 4 nanoparticles prepared via typical coprecipitation routes, which renders these materials interesting for applications in the biomedical field. The formation of magnetite nanoparticles within chitosan using the coprecipitation route was found to be dependent on the concentration of this polysaccharide (Hernandez et al, 2009). Above a chitosan content of 3 wt%, a non magnetic iron hydroxide was formed instead of magnetite.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 96%
“…This is an important outcome since maghemite, the product that results in this case from the oxidation of magnetite, has lower saturation magnetization than magnetite. Magnetic iron oxide nanoparticles have been also synthesized in the presence of other polysaccharides such as starch (D. K. Kim et al, 2003), alginate (Morales et al, 2008;Naik et al, 2005), dextran (Dou et al, 2008) and chitosan (Hernandez et al, 2009), using the coprecipitation method. The presence of starch molecules limited the size of the Fe 3 O 4 nanoparticles to 6 nm and the agglomeration of the coated nanoparticles was controlled upon the cleavage of the glycosidic bonds of the polymer, which allowed preparing magnetic composite particles with average size smaller than commercially available dextran-coated magnetic nanoparticles.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…The storage (elastic) modulus (G′) and loss (viscous) modulus (G′) were measured for gel formulations. 31,32 The storage modulus as a function of frequency for chitosan hydrogels of varying nanoparticle concentrations are presented in Figure 5. Altering the concentration of nanoparticles dramatically changed the viscoelastic properties of the gel.…”
Section: Preparation and Characterization Of Gelsmentioning
confidence: 99%
“…differences could indicate an increase of the thermal stability associated to the sample containing AgNP [8]. Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Chitosan is a cationic aminopolysaccharide obtained by the alkaline deacetylation of chitin, it presents several characteristics such as bioadhesivity, biodegradablility, biocompatibility, safety, non-toxicity and it promotes drug absorption. All the previously mentioned characteristics make chitosan a factible option to transport silver nanoparticles [8]. Sanpui et al and Rhim et al have reported the preparation of different chitosan-Ag composites [9,10], however the way chitosan and silver nanoparticles are combined is different to ours and what they prepared are nanoparticles suspensions (where silver nanoparticles are covered with chitosan molecules) or films which are not as maneagable as a gel when it comes about possible oral or skin treatment applications.…”
Section: Introductionmentioning
confidence: 93%